2022
DOI: 10.48550/arxiv.2201.01471
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Deterministic improvements of quantum measurements with grouping of compatible operators, non-local transformations, and covariance estimates

Abstract: Obtaining the expectation value of an observable on a quantum computer is a crucial step in the variational quantum algorithms. For complicated observables such as molecular electronic Hamiltonians, a common strategy is to present the observable as a linear combination of measurable fragments. The main problem of this approach is a large number of measurements required for accurate estimation of the observable's expectation value. We consider several partitioning schemes based on grouping of commuting multi-qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(23 citation statements)
references
References 20 publications
0
23
0
Order By: Relevance
“…Among various heuristics for grouping commuting Pauli products 7,10,16 we used the Sorted Insertion (SI) method 3 because it generally outperforms other grouping techniques in the number of measurements. 4,5 Since measurement circuits for Ûi of the FC and QWC groups can be constructed using only Clifford group transformations, according to the Gottesman-Knill theorem these circuits can be implemented efficiently on both classical and quantum computers. 17,18 For the FC grouping an asymptotically optimal scaling of O(N 2 q / log(N q )) in the number of 2qubit entangling gates and single qubit rotations can be achieved.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among various heuristics for grouping commuting Pauli products 7,10,16 we used the Sorted Insertion (SI) method 3 because it generally outperforms other grouping techniques in the number of measurements. 4,5 Since measurement circuits for Ûi of the FC and QWC groups can be constructed using only Clifford group transformations, according to the Gottesman-Knill theorem these circuits can be implemented efficiently on both classical and quantum computers. 17,18 For the FC grouping an asymptotically optimal scaling of O(N 2 q / log(N q )) in the number of 2qubit entangling gates and single qubit rotations can be achieved.…”
Section: Resultsmentioning
confidence: 99%
“…Recent comparisons of state-of-theart techniques in the two categories shown that one can achieve a lower number of the measurements using techniques within the qubit operator algebra. [4][5][6] These qubit techniques are based on partitioning of the Hamiltonian to sets of commuting Pauli operators. [6][7][8][9][10] Due to differences in accuracy of performing one-and two-qubit transformations in quantum computers, it is convenient to distinguish two types of commutativity, general or full commutativity (FC) and a more restrictive qubit-wise commutativity (QWC).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As of today, the best method to experimentally estimate an expectation value O is unclear. Besides Pauli grouping [4][5][6][7][8][9][10][11][12][13], there is active research in addressing this problem with classical shadows [14][15][16][17], unitary partitioning [18,19], low-rank factorization [20], adaptive estimators [21][22][23], and decision diagrams [24].…”
Section: Introductionmentioning
confidence: 99%
“…(see SM [29,IV]). In this letter, we focus on grouped Pauli measurements (GPMs) which are more efficient than individual Pauli measurements (IPMs) [4][5][6][7][8][9][10][11][12][13]. To quantify this advantage, Crawford et al [9] introduce a figure of merit, called R, which approximates the difficult to compute quantity R = N shots IPM /N shots GPM , where N shots IPM is the number of shots that IPMs would require to estimate O to a desired accuracy and similarly for N shots GPM .…”
mentioning
confidence: 99%